2012
DOI: 10.4103/2045-8932.94832
|View full text |Cite
|
Sign up to set email alerts
|

Depolarization‐Dependent Contraction Increase after Birth and Preservation following Long‐Term Hypoxia in Sheep Pulmonary Arteries

Abstract: Membrane depolarization is critical to pulmonary arterial (PA) contraction. Both L-type Ca2+ channels (CaL) and Rho-kinase are important signaling components of this process and mitochondrial and non-mitochondrial generated superoxides can be part of the signaling process. Maturation and long-term hypoxia (LTH) each can modify depolarization-dependent contraction and the role of superoxides. By the use of wire myography, we tested the hypothesis that maturation and LTH increase pulmonary arterial reactivity to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(50 citation statements)
references
References 44 publications
6
42
2
Order By: Relevance
“…Furthermore, PKG inhibits RhoA activity, which is a key modulator of the Rho kinase pathway (27,49). This is directly relevant to the current studies, as we previously showed that Rho kinase accounts for roughly half of the arterial tension due to serotonin or membrane depolarization in pulmonary arteries of sheep (10,68). Future studies are therefore needed to discriminate the interaction between PKG and various pathways.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, PKG inhibits RhoA activity, which is a key modulator of the Rho kinase pathway (27,49). This is directly relevant to the current studies, as we previously showed that Rho kinase accounts for roughly half of the arterial tension due to serotonin or membrane depolarization in pulmonary arteries of sheep (10,68). Future studies are therefore needed to discriminate the interaction between PKG and various pathways.…”
Section: Discussionmentioning
confidence: 91%
“…Many of the experimental procedures and protocols are based on our previously published methodology Papamatheakis et al, 2011Papamatheakis et al, , 2012Papamatheakis et al, , 2013Blood et al, 2013). All animals were purchased from Nebeker Ranch (Lancaster, CA; 720 m elevation).…”
Section: Experimental Animalsmentioning
confidence: 99%
“…The normoxic control animals were brought to LLU (353 m elevation; ewe arterial PaO 2 = 95 -5 Torr) for experimental study. The chronic hypoxic experimental animals were acclimatized to high altitude (3801 m elevation, ewe PaO 2 = 60 -5 Torr) at the Barcroft Laboratory, White Mountain Research Station (Bishop, CA), for *110 days (Longo et al, 1996;Goyal et al, 2011;Papamatheakis et al, 2012). …”
Section: Experimental Animalsmentioning
confidence: 99%
See 2 more Smart Citations